The Transformation of Critical Land Governance Based on the Islamic Spirituality Values - Moh Muslih; Aenurofik Aenurofik (Jurnal Penelitian, 2022)
This study aims to transform critical land governance based on Islamic spiritual values contained in the community's economic importance and environmental conservation values. This study used the Participatory Action Research (PAR) method, which was taken through 2 stages, each consisting of 4 procedures. The research involved the community in Dawuhan Village, Sirampog District, Brebes Regency, who worked together to solve problems regarding critical land. The research results show that the management of fundamental land transformation is carried out through coffee planting. This transformation is based on environmental conservation values and community economic values. The minimization of critical land status in Dawuhan village shows the importance of environmental conservation. In contrast, the economic value of the people in Dawuhan village has increased sharply after the transformation of management. The minimization of the status of critical land in Dawuhan Village is known from the increase in land planted with thorny trees (pine, coffee, and so on) from 20% to 30%. The increase in the economic value of the people in Dawuhan Village is shown by the increase in coffee yields from 1 ton to 5 tons. The growth around perennials and the economy was obtained after the implementation of the PAR conducted in this study.